Depth‐dependence of visual signals in the human superior colliculus at 9.4 T. Issue 1 (23rd September 2016) - Loureiro, Joana R.; Hagberg, Gisela E.; Ethofer, Thomas; Erb, Michael; Bause, Jonas; Ehses, Philipp; Scheffler, Klaus; Himmelbach, Marc
Abstract: The superior colliculus (SC) is a layered structure located in the midbrain. We exploited the improved spatial resolution and BOLD signal strength available at 9.4 T to investigate the depth profile of visual BOLD responses in the human SC based on distortion‐corrected EPI data with a 1 mm isotropic resolution. We used high resolution (350 µm in‐plane) anatomical images to determine regions‐of‐interest of the SC and applied a semi‐automated method to segment it into superficial, intermediate, and deep zones. A greater than linear increase in sensitivity of the functional signal at 9.4 T allowed us to detect a statistically significant depth pattern in a group analysis with a 20 min stimulation paradigm. Descriptive data showed consistent depth profiles also in single individuals. The highest signals were localized to the superficial layers of the right and left SC during contralateral stimulation, which was in good agreement with its functional architecture known from non‐human primates. This study thus demonstrates the potential of 9.4 T MRI for functional neuroimaging even in deeply located, particularly challenging brain structures such as the SC. Hum Brain Mapp 38:574–587, 2017 . © 2016 Wiley Periodicals, Inc.